Studi Literatur: Manajemen Pendidikan Berbasis Kearifan Lokal Banjar dalam Penguatan Karakter Siswa - Verdian Wirtung; Ana Fitrotun Nisa (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Character education is a key pillar of the Indonesian education system. Technological developments and the rapid flow of globalization pose significant challenges to the character development of students, particularly in the era of information disruption, which often shifts the nation's moral values. Schools are expected to serve not only as institutions for the transfer of knowledge but also as centers for the formation of noble personalities. One strategic approach to strengthening character education is the integration of local wisdom. Banjar traditions such as the